Intelligence, Personality, and the Prediction of Life Outcomes: Borghans et al. (2016) vs. Zisman and Ganzach (2022) Debate - Lazar Stankov (Journal of Intelligence, 2023)
This article examines the psychological measures employed in studies that compared the predictive validity of personality and intelligence for important life outcomes and came to divergent conclusions. At least some discrepant findings can be accounted for by the fine-grained analysis of measures employed in the assessment of intelligence and personality. The use of Big Five measures of personality traits for predicting life outcomes appear to be poorly supported—other ways of assessing personality need to be explored. Methods used to study cause–effect relationships in non-experimental studies will need to be employed in future.